The role of matrix metalloproteinases in the myocardial remodeling - Vladlen V. Bazylev (Concilium Medicum, 2020)
The main structural event in the development of heart failure is the myocardial remodeling. The extracellular matrix, that was knows as, considered an inert framework of cardiomyocytes, plays an important role in cardiac remodeling. The enzyme system, primarily responsible for the degradation of the extracellular matrix, is a matrix metalloproteinases (MMP). This review examines the evidence for the participation of MMP in the myocardial remodeling and recent studies of MMP as prognostic markers. Regulation of induction and/or activation of MMP are potential therapeutic targets.